Direct Transfer Manufacturing of Flexible Silicon Carbide Nanowire-Network Prototype Device - TEKER, KAŞİF (My University, 2022)
Flexible and transparent devices are expected to meet increasing consumer demands for upgrades in wearable devices, smart electronic and photonic applications. In this work, nanomanufacturing of a flexible and powerless silicon carbide nanowire network ultraviolet photodetector (SiCNW-network UVPD) prototype was investigated by a very cost-effective direct transfer method. Indeed, the powerless device exhibited a photo-to-dark current ratio (PDCR) of 15 with a responsivity of 5.92 mA/W at 254 nm wavelength exposure. The reliability and durability of the device was evaluated by bending tests. In fact, the PDCR of the device was still very good even after seventy-five bending cycles (similar to 96 % of the rest state). In brief, our flexible, powerless SiCNW-network UVPD device with cost-effectiveness, good performance, and durability can provide feasible alternatives for new generation wearable optoelectronic products.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Yüzeyler ve arayüzeyler; İnce filmler ve nanosistemler; Temel Bilimler; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Surfaces, Interfaces, Thin Films and Nanosystems; Natural Sciences; NANOBİLİM VE NANOTEKNOLOJİ; Temel Bilimler (SCI); NANOSCIENCE & NANOTECHNOLOGY; PHYSICS; Natural Sciences (SCI); Flexible electronics; SiCNW-network; Wearable photonic applications; Direct transfer method; ULTRAVIOLET PHOTODETECTOR; FABRICATION; ELECTRODES; COATINGS